Cancer patient satisfaction regarding the quality of information received: psychometric validity of EORTC QLQ-INFO25 - Michele Bezerra; Edvane Birelo Lopes De Domenico (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to psychometrically validate the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire EORTC QLQ-INFO25 instrument and identify the domains that influence patients' perception of the information received. Methods: a cross-sectional methodology with cancer patients in a Brazilian philanthropic hospital institution. Sociodemographic and clinical instruments, EORTC QLQ-C30, EORTC QLQ-INFO25 and Supportive Care Needs Survey - Short Form 34 were used. Analysis occurred using Cronbach's alpha coefficients, intraclass correlation, test-retest and exploratory factor analysis. Results: 128 respondents participated. Cronbach's alpha coefficient was 0.85. The test-retest obtained p-value=0.21. In the factor analysis, one item was excluded. Satisfaction with the information received was 74%, with three areas with averages below 70%. In open-ended questions, there was a greater desire for information. Conclusions: validity evidence was obtained with instrument reliability, consistency and stability. Respondents expressed satisfaction with the information received.